CLINICAL STUDY ON ORAL HYGIENE IN PATIENTS WITH FIXED DENTAL PROSTHESES - Zinovia Surlari; Dragoș-Ioan Virvescu; Balcoș Carina; Cristina Iordache; Dana-Gabriela Budală; Elena Luca; Mihaela Scurtu; Oana Țănculescu (Romanian Dental Association for Education, 2020)
Aim of the study The aim of the study was to asses and increase the awareness and the knowledge regarding oral hygiene practice in patients with fixed dental protheses. Materials and method We performed a study in a cohort of fifty-four consecutive patients with FDPs, aged 25-55, attending the Fixed Prosthodontics Department during October 2017 - September 2019. Results Twenty (37%) patients do not use any oral hygiene aids to clean the prosthesis, the rest 34 (63%) using dental floss, mouthwash, interdental brushes or a combination of them Conclusions The main reason for not using any dental cleaning aids might be the lack of oral health instruction, the patients not being informed by the dentists, but also economical factor and the patient's education and social background.